The role of Social Capital in Enabling Individuals in Continuous Development - Ahmed Thamer khayoon, Lect. Dr (lark, 2023)
In this research, we know about the concept of social capital and how it relates to the empowerment of individuals and development through enhancing production, combating poverty, and building a culture of tolerance and trust within society, and what is the reality of capital in our  societies.  The social capital is considered one of social strength standards which  contributes in building cohesive community and building developmental personality With all its features of values ,standards, and social virtues that make the personality  more belonging and participatory.  Thus, social capital contributions to organize the individual to achieve development, efficiency and effectiveness of planning, follow-up, evaluation, decision-making and mobilize  efforts.
Keywords: Social capital, empowerment, and developm.